Aplikasi Model Adaptasi Roy pada Anak dengan Ruam Popok - Susiana Jansen; Elfira Awalia Rahmawati (Jurnal Keperawatan Silampari, 2023)
This study aims to provide an overview of the application of Roy's adaptation model to children who experience skin integrity damage in the form of diaper rash. The research method used was a case study on five pediatric patients. Based on Roy's adaptation model, nursing care begins with a behavioral assessment of physiology, self-concept, role function, and interdependence. The evaluation is continued with a stimulus assessment consisting of focal, contextual, and residual stimuli. After obtaining data based on the review, the authors formulate nursing problems that arise based on whether the child's response is adaptive or ineffective. Nursing interventions and evaluations are based on the Indonesian Nursing Diagnosis Standards (IDHS) nursing care. The results showed that Roy's adaptation model was recommended for providing nursing care to children with damaged skin integrity through diaper rash. In conclusion, nursing care using the Roy adaptation model can be implemented in pediatric patients with problems with impaired skin integrity in the form of diaper rash. Keywords: Children, Impaired Skin Integrity, Model Roy, Diaper Rash